Functional properties of Saccharomyces kluyveri Y97-fermented solo black garlic - SETIYONINGRUM, FITRI; PRIADI, GUNAWAN; HERLINA, NINA; SOLIKHIN, AKHMAD; LISANI, NURUL (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2018)
Setiyoningrum F, Pribadi G, Afiati F, Herlina N, Solikhin A, Lisani N. 2018. Functional properties of Saccharomyces kluyveri Y97-fermented solo black garlic. Asian J Agric 2: 48-51. Saccharomyces kluyveri Y97-fermented solo black garlic was made by fermentation of fresh solo garlic in medium containing S. kluyveri aging in 70C and relative humidity close to 60%. The fermentation period of fresh solo garlic in the medium was 0, 2, 4 dan 6 days. The black aging period was 0 (fresh garlic), 7, 14 dan 21 days. Antioxidant capacity, flavonoid content and total poliphenol were observed. S. kluyveri Y97-fermented solo black garlic had higher antioxidant capacity, flavonoid content and total polifenol compared to solo black garlic without fermentation. Fermentation of fresh solo garlic by S. kluyveri Y97 before aging process could increase solo black garlic’s functional properties.